Factors for the Growth of Pharmaceutical Expenditures Reimbursed by Public Funds: Methods and Models for Reducing Them - Tsvetkov, Veselin (Research Papers, 2009)
This paper discuses some of the economic factors for the growth of pharmaceutical expenditures in the end of the last and the beginning of the 21 century. It gives special attention to inequality of income allocation as a factor for implementing comprehensive health insurance coverage. It is demonstrated that this process lead to increasing of the rate of moral hazard of costumers and thus to the growth of pharmaceutical expenditures. The market failures typical for pharmaceutical market have been analyzed as additional causes for government influence. Methods and models for restricting the pharmaceutical expenditures in public sector, available in developed countries, are discussed. The measures influencing supply, demand and pure market tools are subject of special attention. As sources are used Bulgarian and International literature, periodicals, monographic issues, scientific researches and Internet stores.